NEW TECHNOLOGIES IN PREVENTIVE PEDIATRICS — ARTERIOGRAPHY - O.S. Logacheva; O.V. Kozhevnikova; L.S. Namazova-Baranova; A.E. Pal'tseva; L.A. Ryzhkova; I.V. Shirokova (Педиатрическая фармакология)
There is currently an increase in the frequency of cardiovascular diseases which are caused by atherosclerotic vessel impairments, such as myocardial infarction and cardiovascular accident. The purpose of this research is to study the possibility of implement into outpatient pediatric practice the method of arteriography for determining changes in the aortic wall at the early development stage. 2 indicators were measured using arteriography: pulse wave velocity and the augmentation index in healthy children aged 6 to 12 years old. The results obtained in a study of healthy children reliably differ from standardized norms for adults and may be used as references.Key words: arteriography, atherosclerosis, arterial rigidity, pulse wave velocity, augmentation index, children.